Religious Tolerance in Islam and Hinduism: A Comparative Analysis of the Holy Qur’an and the Vedas - Rohmah, Nazilatur (Prodi Studi Agama-Agama, 2025)
This article considers the importance of religious tolerance especially in Islam and Hinduism amid religious conflicts and social tensions that often arise as a result of miscommunication with other religious teachings, especially in pluralistic societies such as Indonesia. The purpose of this study is to examine the concepts of religious tolerance taught in Islam and Hinduism through analysis of the holy scriptures of the Qur 'an and Veda. From qualitative methods with comparative approach and literature studies, this study shows that Islam and Hinduism both emphasize the importance of honoring differences, justice, and harmony in a common life. However, there is a difference in the theological approach, where Islam emphasis more on constancy, while Hinduism is more inclusive of its various spiritual pathways. It is hoped that the study can strengthen cross-religious understanding, enhance interfaith dialogue, and promote harmonious and peaceful social harmony.